Toxicological analysis on EGFR Protein Inhibitors (Clerodane) using TOPKAT analysis. - RAVIKUMAR M; JEYANTHI REBECCA L; XAVIER SURESH; ANANTHI RACHEL L (International Journal of Pharma and Bio Sciences, 2012)
The epidermal growth factor receptor (EGFR) is under investigation as a therapeutic target for cancers. Lung cancer cell lines are variably dependent on autocrine stimulation of EGFR since it has a role in signal transduction .We therefore examined the effects of a selective EGFR tyrosine kinase inhibitor Clerodane. Clerodane molecule was used as an inhibitor for EGFR and it was extracted from Tinospora cordifoli(common name-Guduchi). These compounds after docking with EGFR protein were found to possess good energy score and also highly inhibited the protein molecule showed anticancer activity on EGFR. Clerodane highly inhibited the protein EGFR at the position of ARG 231 & CYS 224 . ADME properties of Clerodane by using ADME tool of TOPKAT (DS 2.5) and the Pharmacokinetics results for Clerodone molecule indicated that molecule is non toxic effect to female mouse and female rat (Norms per NTP carcinogenicity). Moreover, as per Food and Drug Administration carcinogenicity value, there is no toxic effect on male rat and male mouse. The pharmacokinetic results showed normal absorption rate, solubility, heptotoxicity, CYP2D6 and PPB values.